The determinants of turkish foreign aid: An empirical analysis - (:unkn) unknown (Palgrave Macmillan, 2020)
This chapter analyzes the interests and motivations in the formulation and implementation of Turkish foreign aid policies by conducting an empirical analysis on data derived from a volume of aid flows from Turkey to 143 countries and five sets of determinants drawing upon 19 different variables of both interval and nominal type. The chapter fundamentally tries to understand economic, humanitarian, political, cultural/religious grounds and regional sensitivity of Turkish humanitarian and development assistance. A panel data has been compiled based on the variables and analyzed in R with a linear regression model. The main findings suggest that Turkish foreign aid allocation depends on a multi-track approach embodying distinct interests and motivations. The economic potential and benefits stand as the crucial determinant of aid flows while humanitarian concerns, official ties, institutionalization of aid, religious and regional affinity are also crucial factors in the decision-making. © 2020, The Author(s).
Keywords: Foreign aid; Humanitarian and development assistance; Turkey; Turkish foreign policy